The whole world was watching : sport in the Cold War - Edelman, Robert, 1945-; Young, Christopher, 1967- (Cold War International History Project series., 2020)
This state-of-the-field volume seeks to understand the cultural phenomenon of sports in the Cold War in its fullest social, political, cultural and global dimensions. Essays from an international lineup of contributors consider sport as a vital sphere for understanding the complex geopolitics and cultural politics of the time, not just in terms of commerce and celebrity, but also with respect to shifting notions of race, class, and gender.